Effect of catfish (Clarias batrachus) bone paste application to changes in enamel surface roughness: Pengaruh aplikasi pasta tulang ikan lele (Clarias batrachus) terhadap perubahan kekasaran permukaan email - Juni Jekti Nugroho (Makassar Dental Journal, 2021)
Background: Demineralization is a condition where the tooth surface experiences mineral loss by releasing the bonds of cal-cium, hydroxyapatite and phosphate compounds thereby increasing the surface roughness of the enamel. Calcium and phos-phate can help improve the remineralization process by rebuilding hydroxyapatite crystals. Catfish (Clarias batrachus) bones contain 5.68% calcium and 3.78% phosphate which potentially remineralize tooth enamel. Objective: To determine the effect of catfish bone paste application on enamel surface roughness. Method: This experimental laboratory research used 32 samples of maxillary first premolar which were divided into 2 groups. All samples were immersed in cola type carbonated drinks for 2 minutes. Samples in each group were treated (6 minutes and 30 minutes) with catfish bone paste application in group I and CPP-ACP application in group II. The roughness test was carried out using a surface roughness tester on the surface of the initial tooth enamel, after soaking it in a cola type carbonated drink, and after application of the remineralization material for 6 mi-nutes and 30 minutes. Results: There was a decrease in enamel surface roughness after application of catfish bone paste and CPP-ACP paste. Conclusion: The application of catfish bone paste significantly decreased enamel surface roughness.